Comparing and the Relationship between Stress and Craving Usage in Addicted to Opium and Industrial Substances - S Fatemeh Poor-seyed M; S vali ollah Mousavi; S Mosa Kafi (Drug Control Headquarters, Research and Education Office, 2013)
Aim: According to the importance of stressful and impellent factors in severity of craving and after that treating successes, this study had done with purpose of examining the relationship between these factors with craving experience in addicted men in six groups (smoking of opium, inhalation of Heroin, smoking of Heroin, injection of Heroin, smoking of methamphetamine, smoking of crack). Method: In this descriptive-sectional study, 195 addicted men had referred to cold turkey centers in Rasht, during 10 months of 1389-1390 selected by available sampling method in six groups. Stress evaluation questionnaire of Markham and the questionnaire of instant craving drug of Franken and also profited by imaginary indexes of computer tests for severity of craving administered among selected samples. Results: The results showed that there is a significant and positive relationship between the stress and cue induction craving, and the stress and instant craving. Also, it proved that there is a significant difference between different users in degree of stress, and inductive craving, and instant craving. The average of stress scores, cue induction craving and instant craving in testing groups of methamphetamine users were more than other groups. Conclusion: According to findings of this survey, stress can be an important predicting factor for craving degree in addicted men so, attention of these aspects resulted in selecting an appropriate treatment of psychology for controlling of craving which is the most important factor leading to relapse in substance abuse.